2000
DOI: 10.1159/000016612
|View full text |Cite
|
Sign up to set email alerts
|

Caries Prediction by Multiple Salivary Mutans Streptococcal Counts in Caries–Free Children with Different Levels of Fluoride Exposure, Oral Hygiene and Sucrose Intake

Abstract: The aims of this study were to assess whether multiple salivary mutans streptococcal (ms) counts have a higher predictive power than a single one, and whether the predictive power of the test is different at different levels of fluoride exposure, oral hygiene and sucrose consumption. Three salivary ms tests were performed at 3–month intervals (positive test: salivary ms ≥5×105 cfu/ ml) on a sample of 304, initially caries–free, 6– to 7–year–olds. Plaque index was also assessed and the parents filled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
2
15
1
Order By: Relevance
“…Several other studies have examined the use of a wider range of factors in caries prediction, involving behavioural and socio-demographic factors. They were included in the prediction models [Demers et al, 1992;Disney et al, 1992;Holbrook et al, 1993] or used as confounders in mutans streptococci tests [Mattiasson-Robertson and Twetman, 1993;Petti and Hausen, 2000]. Their analyses predicted between 48.4 and 82.8% of high increment children (sensitivity) and between 70 and 93.7% of the low increment children (specificity).…”
Section: Risk Predictorsmentioning
confidence: 99%
“…Several other studies have examined the use of a wider range of factors in caries prediction, involving behavioural and socio-demographic factors. They were included in the prediction models [Demers et al, 1992;Disney et al, 1992;Holbrook et al, 1993] or used as confounders in mutans streptococci tests [Mattiasson-Robertson and Twetman, 1993;Petti and Hausen, 2000]. Their analyses predicted between 48.4 and 82.8% of high increment children (sensitivity) and between 70 and 93.7% of the low increment children (specificity).…”
Section: Risk Predictorsmentioning
confidence: 99%
“…In order to estimate the power of vaccination to predict actual immuni ty against HBV, the methodology to assess the predictive power of screening tests was used 20 . Namely, true positive rate (TPR, i.e., Sensitiv ity) was the proportion of immune individuals who declared to be vaccinated; false negative rate (FNR, i.e., "1-Sensitivity") was the propor tion of immune individuals who declared not to be vaccinated; true negative rate (TNR, i.e., Specificity) was the proportion of non-immune individuals who declared not to be vaccinated; false positive rate (FPR, i.e., "1-Specificity") was the proportion of non-immune individuals who declared to be vaccinated; Accuracy (i.e., the proportion of correctly predicted as pro tected or non-protected).…”
Section: Methodsmentioning
confidence: 99%
“…Eight cohort studies in nine publications were identified that presented evidence on the relationship between the frequency of consumption of sugars-containing foods and/ sugars confectionery and the incidence of caries in the mixed/permanent dentition, five of which adjusted their results for tooth brushing (Mattila et al, 2001;Leroy et al, 2005;Mattila et al, 2005;Kallestal & Fjelddahl, 2007;Ollila & Larmas, 2007;Tamaki et al, 2009) and three of which that did not (Wilson & Ashley, 1989;Petti & Hausen, 2000;Bruno-Ambrosius et al, 2005). Two articles reported on same cohort (Mattila et al, 2001;Mattila et al, 2005), which followed-up a birth cohort until the children were 10 years of age.…”
Section: Sugars-sweetened Beverages and Bmimentioning
confidence: 99%